1998
DOI: 10.1097/00003246-199808000-00015
|View full text |Cite
|
Sign up to set email alerts
|

Do autopsies of critically ill patients reveal important findings that were clinically undetected?

Abstract: Although the primary clinical diagnosis was accurate in most cases before death, the cause of death was frequently unknown. Almost all autopsies demonstrated new diagnoses, and knowledge of these new findings would have changed medical ICU therapy in many cases. In the critical care setting, autopsies continue to provide information that could be important for education and quality patient care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
67
3
7

Year Published

2000
2000
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 100 publications
(82 citation statements)
references
References 15 publications
5
67
3
7
Order By: Relevance
“…Such diagnostic disagreement can vary from 10 to 90%, depending on the disease and the population involved. (6)(7)(8)(9)11,18) These discrepancies might be attributable to different clinical manifestations of a single disease and to poor quality medical care. (9) However, recent studies have demonstrated the value of autopsy in medical education, in the evaluation of medical procedures, in physiopathology, in epidemiology, in public health and in the evaluation of the treatment employed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Such diagnostic disagreement can vary from 10 to 90%, depending on the disease and the population involved. (6)(7)(8)(9)11,18) These discrepancies might be attributable to different clinical manifestations of a single disease and to poor quality medical care. (9) However, recent studies have demonstrated the value of autopsy in medical education, in the evaluation of medical procedures, in physiopathology, in epidemiology, in public health and in the evaluation of the treatment employed.…”
Section: Discussionmentioning
confidence: 99%
“…(9) However, recent studies have demonstrated the value of autopsy in medical education, in the evaluation of medical procedures, in physiopathology, in epidemiology, in public health and in the evaluation of the treatment employed. (1,(6)(7)(8)10,11,(26)(27)(28)(29) Nevertheless, and specifically in pediatrics, autopsy can detect genetic diseases, allowing better counseling of the family. (7,9) Regarding issues such as whether to take into account the value of autopsy in medical education and medical procedures, and considering that many of the postmortem findings might have influenced treatment during the life of the patient and prevented the death of other patients, our study has limitations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, studies show that the incidence of diagnostic errors remained relatively constant [23, 49,55], and autopsy is a fundamental tool of quality control in medical practice [5,34,25,26].…”
Section: Introductionmentioning
confidence: 99%
“…The general rates of discrepancy between ante and post mortem diagnosis identified by various research varies between 10 and 50% depending on the postmortem examination criteria, the complexity of the necropsy, the methods used for the assessment of the differences and the studied population [5,6,31,34,39,41,45,54,11].…”
Section: Introductionmentioning
confidence: 99%